Public-Private Partnerships in Smart City Development: A Bibliometric Analysis with a Sustainability Perspective - Putri, Ersha Aisyah; Anwar, Rully Khairul; Winoto, Yunus (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
This study explores how Public-Private Partnerships (PPPs) analyzed through a sustainability-oriented perspective through a bibliometric approach. It reviews keyword trends, countries, and institutions actively involved in this field to provide insights into how such collaborations can enhance public service quality. Data was collected from the Scopus database for the 2014–2024 period, yielding 650 publications analyzed using Biblioshiny software in RStudio. The findings reveal a growing research trend, with China leading in publication contributions, while Australia ranks highest in citations. This study highlights the importance of integrating sustainability values into public-private collaborations, particularly to support smart city development focusing on environmentally friendly technologies and societal well-being. The research also provides recommendations for future studies and policies that support sustainable development.